Current standards of neuropsychological assessment in epilepsy surgery centers across Europe. (9th January 2017) - Vogt, Viola Lara; Äikiä, Marja; del Barrio, Antonio; Boon, Paul; Borbély, Csaba; Bran, Ema; Braun, Kees; Carette, Evelien; Clark, Maria; Cross, Judith Helen; Dimova, Petia; Fabo, Daniel; et al.
Summary: We explored the current practice with respect to the neuropsychological assessment of surgical epilepsy patients in European epilepsy centers, with the aim of harmonizing and establishing common standards. Twenty‐six epilepsy centers and members of "E‐PILEPSY" (a European pilot network of reference centers in refractory epilepsy and epilepsy surgery), were asked to report the status of neuropsychological assessment in adults and children via two different surveys. There was a consensus among these centers regarding the role of neuropsychology in the presurgical workup. Strong agreement was found on indications (localization, epileptic dysfunctions, adverse drugs effects, and postoperative monitoring) and the domains to be evaluated (memory, attention, executive functions, language, visuospatial skills, intelligence, depression, anxiety, and quality of life). Although 186 different tests are in use throughout these European centers, a core group of tests reflecting a moderate level of agreement could be discerned. Variability exists with regard to indications, protocols, and paradigms for the assessment of hemispheric language dominance. For the tests in use, little published evidence of clinical validity in epilepsy was provided. Participants in the survey reported a need for improvement concerning the validity of the tests, tools for the assessment of everyday functioning and accelerated forgetting, national norms, and test co‐normalization. Based on the present survey, we documented a consensus regarding the indications and principles of neuropsychological testing. Despite the variety of tests in use, the survey indicated that there may be a core set of tests chosen based on experience, as well as on published evidence. By combining these findings with the results of an ongoing systematic literature review, we aim for a battery that can be recommended for the use across epilepsy surgical centers in Europe.